Analysis of Togel Gambling as a Crime from an Islamic Criminal Law Perspective - Dinda Suciana Rambe; Harafi Pasaribu (AT-TAFAHUM: Journal of Law, 2025)
In Indonesian society, gambling remains a controversial issue. Law enforcement has uncovered numerous cases. This demonstrates that gambling in Indonesia has not been eradicated and is a social ill. Gambling involves deliberate wagering, risking a value or something deemed valuable, while acknowledging the risks and expectations inherent in games, matches, competitions, and other events with uncertain outcomes. Verse 90 of QS Al-Maidah clearly forbids gambling, citing its heinous nature as a satanic act. Therefore, we should refrain from engaging in it. Research methodology is a collection of regulations, activities, and procedures employed by practitioners of a discipline. This type of research is normative legal research, also often referred to as library research. Within the framework of the maqāṣid al-syarī'ah (the principles of Islamic law), gambling clearly contains elements of harm that outweigh its benefits. Therefore, prevention and control efforts need to be comprehensive, encompassing legal, social, and religious approaches. In this context, the implementation of legal sanctions for lottery gambling according to the perspective of Islamic criminal law is categorized as ta'zir sanctions, either in the form of caning or other punishments. In addition, sanctions for perpetrators of gambling who use technology, the government can adjust regulations based on applicable laws.